Diagnosis and treatment of isolated rib Langerhans cell histiocytosis in an adult: A case report - Guo, Yaxin; Huang, QiFeng (Frontiers in Surgery, 2023)
Langerhans cell histiocytosis (LCH) was first proposed in 1987 to define the disorder characterized by proliferation of abnormal Langerhans cells. It is more likely to occur in children < 15 years of age. Single-site and single-system LCH of rib is rare in adults. We present a rare case of isolated rib LCH in a 61-year-old male patient and expound the diagnosis and treatment of the disease. A 61-year-old male patient presented with a 15-day history of dull pain in the left chest was admitted to our hospital. PET/CT image showed obvious osteolytic bone destruction and abnormal FDG uptake (maximum standardized uptake value: 14.5) in the right fifth rib with local soft tissue mass formation. The patient was eventually confirmed the diagnosis of LCH by immunohistochemistry stain and treated with rib surgery. A thorough review of the literature regarding diagnosis and treatment of LCH is presented in this study.